Technical Change and the Wage Structure During the Second Industrial Revolution : Evidence from the Merchant Marine, 1865-1912 - Aimee Chin; Chinhui Juhn; Peter Thompson (Institute for the Study of Labor (IZA), 2004)
Using a large, individual-level wage data set, we examine the impact of a major technological innovation – the steam engine – on skill demand and the wage structure in the merchant shipping industry. We find that the technical change created a new demand for skilled workers, the engineers, while destroying demand for workers with skills relevant only to sail. It had a deskilling effect on production work – able-bodied seamen (essentially, artisans) were replaced by unskilled engine room operatives. On the other hand, mates and ablebodied seamen employed on steam earned a premium relative to their counterparts on sail. A wholesale switch from sail to steam would increase the 90/10 wage ratio by 40%, with most of the rise in inequality coming from the creation of the engineer occupation.
Keywords: H52; J62; I21; 330; wage inequality; skill premium; skill-biased technical change; Technischer Fortschritt; Lohnstruktur; Industrialisierung; Schifffahrt; Kanada: Atlantikküste